Existentialism through the Literary Images in the Short Stories of V. Pidmohylny and M. Yatskiv - Karivets, Ihor; Kadykalo, Andrii (Problemos, 2024)
This article analyses little-known short stories of modern Ukrainian writers Valerian Pidmohylny and Mykhailo Yatskiv in the context of the 20th century existentialism. It can be considered as a cultural phenomenon which combines philosophy with literature. Pidmohylny’s short stories were significantly influenced primarily by the ideas of the European philosophers of the late 19th and early 20th centuries. Therefore, we can search for similar motives in the works of Pidmohylny and the existentialists, which developed under the influence of the ideas of Schopenhauer, Kierkegaard, and Nietzsche. Also, the authors consider Yatskiv’s short stories through the prism of the core concepts of existentialism, namely, fate and death. Pidmohylny and Yatskiv can be assigned to existential writers on the basis of retrospective analysis of the themes of their short stories and the thematic areas of 20th century existentialism.